ENTERPRISE RISK MANAGEMENT: A REVIEW OF TWO DECADES - Poorni Sakrabani; Teoh Ai Ping (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This paper is a modest review spanning a 20-year period on Enterprise Risk Management. Enterprise Risk Management (ERM) deals with risks and opportunities which have an impact on value creation. Unlike traditional risk management (TRM) which is silobased, ERM is a holistic approach to risk management. Past studies have produced many contradicting results on the impact of ERM implementation on firm performance and also on the factors which are crucial for the successful implementation of ERM. As such, it is of absolute necessity to identify the determinants of ERM implementation and also how ERM improves performance. The research methodology for this paper began with a literature search for ERM-related articles from journals of various rankings from 2000 to 2020. Relevant papers for the review were selected by using the `going backward’ and `going forward’ process. Fifty research papers were selected in this manner for this review. Prior studies have used different variables to show how implementation of ERM can create value. Further, in recent years, there has been an increase in studies reporting the importance of strong ERM and its link with performance. Although only fifty research papers were reviewed for this paper, yet a few gaps in the extant literature on ERM have been identified. As such, suggestions on how future research can be conducted in this field are given at the end of the review.